Effects of Aglaia odorata granules on the seedling growth of major maize weeds and the influence of soil type on the granule residue's efficacy - CHAMROON LAOSINWATTANA; MONTINEE TEERARAK; PATCHANEE CHAROENYING (My University, 2012)
This study was undertaken to explore the potential of Aglaia odorata Lour. granules in various soil types (sand, sandy loam and clay) at 0.25, 0.5 and 1 t ai ha −1 to inhibit two major maize weeds, Digitaria adscendens and Trianthema portulacastrum L., in an experimental greenhouse. The results indicated that the emergence and seedling growth of both weeds were inhibited but varied with the soil type: the inhibitory effect of the A. odorata granules was stronger when applied in sand, followed by sandy loam and clay. The weed species responded differently to the A. odorata granule application. Generally, the inhibitory effect was greater for D. adscendens than for T. portulacastrum . Additionally, the potential of the A. odorata granules for weed control in maize field plots was evaluated. The three major weeds that were found in the experimental field were D. adscendens , T. portulacastrum and Amaranthus gracilis . The highest A. odorata granule dose (1 t ai ha −1 ) had a significant inhibitory effect on the emergence and growth of all of the weed species and their emergence was reduced by 96.7%, 47.2% and 56.2%, respectively, compared with the control treatment (unweeded). The dry weight of the weeds was reduced in a similar manner to their emergence. In contrast, the emergence of maize was not affected by any of the A. odorata granule applications. Rather, at an application rate of 1 t ai ha −1 , the maize yield increased significantly and the effect was similar to that observed with an atrazine herbicide application under field conditions.
Keywords: Granule (geology); Weed Control and Herbicide Applications